On the diffusivity of ring polymers. Issue 9 (14th February 2020) - Wong, Chi Pui Jeremy; Choi, Phillip
Abstract : The crossover in diffusion coefficients of ring polyethylene is explained by a free volume theory. Abstract : A free volume theory of linear polyethylene (PE) melts [ Soft Matter, 2019, 15, 9300–9309] was used to describe the crossover in the size dependence of the center-of-mass diffusion coefficients of ring PE melts from D cm ∼ N −1.03±0.15 to D cm ∼ N −1.88±0.14 at N c ≈ 100. Parameters in the theory were determined theoretically by either the polymer reference interaction site model (PRISM) theory or molecular dynamics (MD) simulation data. The former method is computationally less expensive, whereas the latter gives more accurate results in calculating the temperature dependence of D cm as different intermolecular and intramolecular potentials were explicitly included in the equation of motion. Both approaches were able to describe the dynamics below and above the crossover in the size dependence of D cm .